Awareness of desired health behaviours as a factor conditioning educational effect by a nurse in the preparation for self-care of patients who had undergone cerebral stroke - Girzelska, Joanna; Kościołek, Aneta; Mianowana, Violetta; Dobrowolska, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The diagnosis of stroke, prognosis and further existence are often a great unknown for patients and their families, with the resulting enormous scope of educational tasks for a nurse. In the prevention of strokes, health education is of great importance aimed at providing patients who had undergone stroke and their families, with skills and knowledge necessary to adopt health promoting behaviours, primarily those contributing to a healthy life style, including non-smoking, moderate alcohol consumption, 7-8 hours of sleep daily, physical activity, normal body mass and others. The aim of the study. The objective of the presented study was determination of awareness of the desired health behaviours among patients who had undergone cerebral stroke, as a factor conditioning the educational effect by a nurse in the preparation for self-care. An attempt was undertaken to provide a reply to the following questions: do the respondents possess knowledge concerning the recommended life style, especially adequate nutrition and physical activity and what are the expectations of patients with respect to knowledge and skills within the recommended life style. Material and methods. The study covered 99 patients treated due to cerebral stroke in the Neurology Ward with the Sub-Ward for Stroke at the Cardinal Stefan Wyszyński Regional Specialist Hospital in Lublin. The study was conducted by the method of a diagnostic survey, with the use of a questionnaire form. Results and conclusions. The results of the survey concerning the respondents’ knowledge with respect to the recommended life style after stroke showed that only 33% of patients in the study possessed essential knowledge, while as many as 66.67% of the group examined were not familiar with the style of life recommended after stroke. Studies concerning nutrition indicted that only 34% of the group examined were familiar with adequate nutrition after stroke, whereas over 65% of respondents showed a deficit of knowledge in this respect. The results of the study confirmed that approximately 57% of patients expect knowledge concerning nutrition. Only about 33% of the group examined would like to obtain knowledge regarding the recommended physical activity and methods of coping with stress. A slightly bigger number of respondents, approximately 26%, wish to become familiar with the methods to reduce body mass. As many as 73.73% of respondents want to get acquainted with the methods to abstain from alcohol consumption. Nursing Topics 2010; 18 (4): 413-419